2021
DOI: 10.3390/ani11041022
|View full text |Cite
|
Sign up to set email alerts
|

Dietary Pomegranate By-Product Alleviated the Oxidative Stress Induced by Dexamethasone in Laying Hens in the Pre-Peak Period

Abstract: This experiment was conducted to assess the inclusion of the by-products of pomegranate peels to ameliorate the harmful impacts of oxidative stress in the pre-peak period of laying hens. For this, 120 local Egyptian strain hens (Inshas hens) aged 24 weeks old were used in four treatments. Pomegranate peel powder was included at 2% and 4% in the diets of laying hens subjected to oxidative injuries induced by dexamethasone compared with negative and positive control groups for 12 weeks. The addition of pomegrana… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
6
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 17 publications
(9 citation statements)
references
References 45 publications
0
6
0
Order By: Relevance
“…The animal capacity to mitigate oxidative stress is critical for the maintenance of egg production and hens’ health, especially in the prepeak period of laying, which can have long-lasting beneficial effects across the production period ( Finkel and Holbrook, 2000 ; Eid et al, 2021 ; Durand et al, 2022 ). Furthermore, it has been recently shown that the PP inclusion used in this work resulted in a consistent expression increase of cytoprotective genes and improved intestinal total antioxidant capacity ( TAC ), as well as an enhanced liver, breast meat and thigh meat TAC in broilers ( Mountzouris et al, 2019 , 2020 ).…”
Section: Discussionmentioning
confidence: 99%
“…The animal capacity to mitigate oxidative stress is critical for the maintenance of egg production and hens’ health, especially in the prepeak period of laying, which can have long-lasting beneficial effects across the production period ( Finkel and Holbrook, 2000 ; Eid et al, 2021 ; Durand et al, 2022 ). Furthermore, it has been recently shown that the PP inclusion used in this work resulted in a consistent expression increase of cytoprotective genes and improved intestinal total antioxidant capacity ( TAC ), as well as an enhanced liver, breast meat and thigh meat TAC in broilers ( Mountzouris et al, 2019 , 2020 ).…”
Section: Discussionmentioning
confidence: 99%
“…In laying hen diets, supplementation with 2-4% pomegranate peel powder improved blood antioxidant activity and reduced plasma cholesterol and triglyceride content [169]. Pomegranate seed oil in hen diets enhanced laying rate, color, and concentrations of punicic acid and CLA in egg yolk [170].…”
Section: Pomegranate By-productsmentioning
confidence: 97%
“…Although the antioxidant activity of PP has been demonstrated by many scientific in vivo studies (Saleh et al, 2017;Al-Shammari et al, 2019;Kishawy et al, 2019;Sharifian et al, 2019;Akuru et al, 2020;Baset et al, 2020;Ahmadipour et al, 2021;Akuru et al, 2021;Eid et al, 2021)in broilers, there is currently no published in vivo research regarding the effects of the combined supplementation of α-tocopherol acetate (TA) and pomegranate peel extract (PPE) to the broiler diets enriched with omega-3 PUFAs.…”
Section: Introductionmentioning
confidence: 99%